An overview of recent remote sensing and GIS based research in ecological informatics - Boyd, Doreen S.; Foody, Giles M. (Elsevier, 2011)
This article provides an overview of some of the recent research in ecological informatics involving remote sensing and GIS. Attention focuses on a selected range of issues including topics such as the nature of remote sensing data sets, issues of accuracy and uncertainty, data visualization and sharing activities as well as developments in aspects of ecological modeling research. It is shown that considerable advances have been made over recent years and foundations for future research established.